The Potential of Vietnam’s Agricultural Exports to the Indian Market: Analysis of Supply and Demand Factors - Trung, Nguyen Xuan; Hien, Nguyen Thi (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">To assess the potential of Vietnam’s agricultural exports to the Indian market through the analysis of trade indicators from analyzing Vietnam’s supply factor and India’s demand factor, the study using Revealed Comparative Advantage (RCA), Export Propensity Index (EPI), Import Penetration Index (IPI) and balance of trade (BOT) on agricultural products in subheadings (6-digit HS code) specified from chapter 1 to chapter 24. The study indicates that Vietnam’s agricultural products with great potential for export to the Indian market are (1) Pepper of the genus Piper, neither crushed nor ground (HS090411); (2) Juniper berries and seeds of anise, badian, caraway, or fennel, neither crushed nor ground (HS090961); (3) Plants, parts of plants, incl. seeds, and fruits, used primarily in perfumery, in pharmacy or for insecticidal, fungicidal or similar purposes, fresh or dried, whether or not cut, crushed or powdered (excluding ginseng roots, coca leaf and poppy straw) (HS121190); (4) Non-alcoholic beverages (excluding water, fruit or vegetable juices and milk) (HS220290); (5) Preparations of a kind used in animal feeding (excluding dog or cat food put up for retail sale) (HS230990). As a result, Vietnamese businesses interested in exporting to India could explore these items.